Evaluation of dacryocystorhinostomy failure with computed tomographic dacryocystography - Jan, Sabhia; ., Apoorva; S. Wani, Junaid; Riaz, Raheel; Nazir, Ovais (International Journal of Research in Medical Sciences, 2017)
Background: The purpose of this study is to evaluate the causes of failure of dacryocystorhinostomy by computed dacryocystography (CT-DCG). Methods: CT-DCG was done in 38 patients of failed DCR of either sex in the age group of 16-60 years, the radiologist blinded to the clinical status of the patient evaluated position and size of bony ostium, soft tissue scarring, bony regrowth, secondary stenosis of canaliculi, synechiae between the ostium and nasal septum and anatomic variations in nasal cavity, turbinates or nasal septum. Results: The most common causes of failure in our study were inappropriate size of osteotomy window in 34 patients (84.47%), inappropriate location of osteotomy window in 31 patients (81.57%), fibrous tissue scarring at osteotomy window in 22 patients (57.89%), the other causes were bilateral concha bullosa in 2 patients, ethmoidal sinusitis in 2 patients, common canalicular block in 1 patient, faulty passage into ethmoidal sinus in 1 patient and no osteotomy window seen in patient. Conclusions: CT-DCG is a valuable imaging tool to evaluate DCR failure before re-operation. In our study CT-DCG showed that small size of osteotomy window, inappropriate position of osteotomy window and fibrous tissue scarring at osteotomy window were frequently seen causative factors of DCR failure.